Cold Tolerance Regulated by the Pyruvate Metabolism in Vibrio parahaemolyticus - Xie, Tengfei; Pang, Rui; Wu, Qingping; Zhang, Juemei; Lei, Tao; Li, Yanping; Wang, Juan; Ding, Yu; Chen, Moutong; Bai, Jianlin (Frontiers in Microbiology, 2019)
Vibrio parahaemolyticus is a common foodborne pathogen found in seafood, and represents a major threat to human health worldwide. Low-temperature storage is an important seafood processing method, but is not sufficient to completely eliminate the bacteria and avoid foodborne illness. To determine the mechanisms behind such cold tolerance, RNA-seq and iTRAQ analyses were first performed to obtain the global transcriptomic and proteomic patterns of frozen squid and clinical V. parahaemolyticus isolates under cold conditions. The integrated analysis revealed the modulation of multiple pathways such as the co-occurrence of down-regulated pyruvate metabolism and up-regulated fatty acid biosynthesis, which likely contribute to V. parahaemolyticus cold tolerance. Furthermore, we found that increasing concentrations of pyruvate can reduce the fatty acid content to influence V. parahaemolyticus growth in cold conditions. Thus, regulation of pyruvate concentration may be an effective method to control this seafood-borne pathogen.